Novel engineering techniques to overcoming traditional challenges in online condition monitoring systems for power transformer. Issue 4 (2nd October 2018) - Chow, Jason; Lee, Ray; Wong, Eric; Leung, Keith; Lai, Gary
ABSTRACT: Traditional challenges in online condition monitoring systems for power transformer are usually due to discrepant results between online condition monitoring system and lab-based measurements (e.g. Dissolved Gas Analysis) and unreliable performance of electronic components due to exposure to harsh outdoor substation environment. As a result, false alarms and service alarms would be generated and extra maintenance efforts are needed to tackle these issues. This will exert additional pressure to frontline staff and engineers. These undesired outcomes are challenges to the implementation of condition monitoring scheme. Several novel engineering techniques and effective contract management method will be presented in this paper to elaborate the ways to overcome these traditional challenges in online condition monitoring systems to ensure effective condition-based maintenance scheme and enhance power supply reliability.